2009
DOI: 10.1080/00036840701367549
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing growth in revenues and costs into price, quantity and total factor productivity contributions

Abstract: This article employs the superlative Fisher and Tornqvist indexes for exact decomposition of growth in nominal revenues and costs. The findings confirm the well-known result that these indexes very closely approximate each other, implying that the mathematically simpler and computationally easier Tornqvist is the more practicable index. Moreover, this article's nominal growth decomposition yields all the results from the more common real growth decomposition and is also more informative for policy purposes. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Change in profitability between any two periods is the change in revenue divided by the change in costs (ΔR/ΔC ). Because profitability is measured as the change between time periods, the individual components can be measured using index numbers [10]. A re-arrangement of terms which make up revenues and costs yields profitability change as (P/W)*(Q/X), where P is an output price index, W is an input price index, Q is an output quantity index, and X is an input quantity index.…”
Section: Methodsmentioning
confidence: 99%
“…Change in profitability between any two periods is the change in revenue divided by the change in costs (ΔR/ΔC ). Because profitability is measured as the change between time periods, the individual components can be measured using index numbers [10]. A re-arrangement of terms which make up revenues and costs yields profitability change as (P/W)*(Q/X), where P is an output price index, W is an input price index, Q is an output quantity index, and X is an input quantity index.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Wu (2020) showed moderate technical efficiency in farms in eastern India. Dumagan and Ball (2009) used Fisher and Törnqvist to study growth decomposition in the agricultural sector of the USA, and concluded that output growth was mainly due to the growth of TFP in the sector. Navin (2014) and Kumar and Shekhar (2017) ascertained than the growth performance of the Indian economy was due to TFP growth.…”
Section: Productivity Growth Decompositionmentioning
confidence: 99%
“…The use of this index is justi ied if the airport does not have the cost of its services (ANAC, 2015, p.14). The Equation 10 was obtained from Dumagan and Ball (2009), due to the amount of data available for the applications of this article.…”
Section: Descrip7on Of the Empirical Modelmentioning
confidence: 99%
“…The aim of this paper is to develop an aeronautical fare pricing model based on airport costs by applying the Tornqvist index and the markup method. The Tornqvist index is found by the calculation of Total Factor Productivity (TFP), being a method to ind the cost of one product according to the factory total cost and quantity produced (Dumagan and Ball, 2009). The speci ics goals are not only to review the applicable pricing policies, reviewing the calculation methods found in the literature, and Brazilian regulations, but also to compare the prices of fares published by Brazilian Aviation Authority Agency (ANAC) with the fare calculated in the application of this paper.…”
Section: Introductionmentioning
confidence: 99%